Adapting to climate change: the social perception of voluntary water transfers in the Italian context. (2015) - Vollaro, Michele; Zavalloni, Matteo; Raggi, Meri; Viaggi, Davide
Climate change is expected to increase the frequency of water scarcity and drought events in Italy. To respond to these challenges, water management in agriculture requires major reforms involving broad public participation. In this paper, we empirically analyse the social perception of climate change and the social acceptability of potential policy reforms of water management in the Italian context. The results show the interviewees' awareness of climate change phenomena and a common consensus on the need to improve efficiency in water management. Furthermore, a positive attitude toward engagement in water exchange mechanisms emerged along with a preference for farm-to-farm and agriculture-private exchanges. Normative and ethical inertias represent the main obstacles for the social acceptability of water markets. Research is needed to address the interactions between social acceptability, economic viability and the implementability of the proposed instruments.